Improvement inEnergy Efficiency of Wireless Sensor Network (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Clustering in wireless sensor network is important to increase the lifetime of sensor network. LEACH protocol is one of the clustering routing protocols in wireless sensor networks. In LEACH each node has the equal probability to be a cluster head, due to which the energy dissipation of every node is balanced. In LEACH protocol, time is divided into many rounds and in each round, all the nodes wishes to be cluster head according to a predefined criterion. This paper focuses on the approach that how could the number of cluster heads are limited in the network, if we limit the number of cluster head to a percentage of total nodes in the network, we can increase the lifetime of the network and decrease the energy dissipation per node. These functions can be used to enhance the performance of cluster-based wireless sensor networks in terms of lifetime and throughput.